2018
DOI: 10.1002/ab.21787
|View full text |Cite
|
Sign up to set email alerts
|

From words to action: Implicit attention to antisocial semantic cues predicts aggression and amygdala reactivity to angry faces in healthy young women

Abstract: Implicit measures of aggressiveness are able to circumvent response biases that plague self-reports, but it is unclear how they link to neural activation during aggressive interactions and to aggression-related endocrine function. Here, we tested whether an implicit attentional bias toward antisocial semantic information was associated with endogenous testosterone (T) and cortisol (C) levels, as well as with aggressive behavior and amygdala reactivity to angry faces in a separate competitive paradigm. On Day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 113 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…Supporting this assumption, persons with more physical aggression and conduct problems appeared to be attracted by more violent combat sports (Vertonghen et al, ). In a competitive reaction time task (Buades‐Rotger & Krämer, ), a positive relationship between the attention to antisocial cues and aggressive behavior was found exclusively in subjects that showed enhanced amygdala activation when viewing angry faces. It should be noted that in this study the subjects were female and that words instead of pictures were used as cues.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this assumption, persons with more physical aggression and conduct problems appeared to be attracted by more violent combat sports (Vertonghen et al, ). In a competitive reaction time task (Buades‐Rotger & Krämer, ), a positive relationship between the attention to antisocial cues and aggressive behavior was found exclusively in subjects that showed enhanced amygdala activation when viewing angry faces. It should be noted that in this study the subjects were female and that words instead of pictures were used as cues.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individuals displaying higher anger tendencies were slower to disengage from hostile words [75] and exhibited difficulties in processing nonhostile information in ambiguously hostile visual scenes [76]. Using neuroimaging data and an emotional word Stroop task, [77] found that attentional bias for antisocial words predicted aggression and that this relationship was fully mediated by amygdala reactivity to angry faces. The present study has also demonstrated a relationship between WM modulated attentional bias and hostile attribution bias.…”
Section: Are Wm Biases Of Visual Selection Predicted By Self-reported Aggression Trait Anger and Hostile Attribution?mentioning
confidence: 97%
“…Moreover, other researchers have posited that the propensity for aggressive behaviors may be linked to attentional biases involved in avoiding threat-relevant stimuli [33,34]. Concurring with this perspective, Buades-Rotger and Krämer [35] used an emotional word Stroop task to examine the relationship between threatening semantic information and aggressiveness, which indicated that a tendency to dwell on implicit risky cues can reflect enhanced aggression. Taken together, the above theorizing and evidence suggest that individuals in a threatening context may behave aggressively.…”
Section: On-line Aggression Toward Stigmatized Groupsmentioning
confidence: 99%